India in the Imagination of 20th and 21st Century Croatian Literature - Molvarec, Lana (Poznańskie Studia Slawistyczne, 2022)
The purpose of this paper is to study perceptions of India in three literary works, from the 20th and 21st century. The first part looks into the tenets of postcolonial theory and literary imagology as a possible methodological framework. Subsequently, premodern perceptions of India in the Croatian literary and cultural space are summarised. The central analysis focuses on the historical novel Jaša Dalmatin (Jaša Dalmatin, Viceroy of Gujarat) by Ivana Brlić-Mažuranić, the travelogue U potrazi za staklenim gradom (In Search of the Glass City) by Željko Malnar and Borna Bebek, and the short story Indija (India) by Bekim Sejranović. The analysis demonstrates that each of these writings reconstructs premodern perceptions to some extent, but primarily introduces new perceptions that are linked to the specific social, cultural and ideological context in which these works were written. This indicates that literary perceptions are at the same time always acts of literary fiction as well as a socially and culturally construed production of meaning.